Ethylene Response Factor (ERF) Family Proteins in Abiotic Stresses and CRISPR–Cas9 Genome Editing of ERFs for Multiple Abiotic Stress Tolerance in Crop Plants: A Review - Debbarma, Johni; Sarki, Yogita N.; Saikia, Banashree; Boruah, Hari Prasanna Deka; Singha, Dhanawantari L.; Chikkaputtaiah, Channakeshavaiah (Molecular biotechnology, 2019)
Abiotic stresses such as extreme heat, cold, drought, and salt have brought alteration in plant growth and development, threatening crop yield and quality leading to global food insecurity. Many factors plays crucial role in regulating various plant growth and developmental processes during abiotic stresses. Ethylene response factors (ERFs) are AP2/ERF superfamily proteins belonging to the largest family of transcription factors known to participate during multiple abiotic stress tolerance such as salt, drought, heat, and cold with well-conserved DNA-binding domain. Several extensive studies were conducted on many ERF family proteins in plant species through over-expression and transgenics. However, studies on ERF family proteins with negative regulatory functions are very few. In this review article, we have summarized the mechanism and role of recently studied AP2/ERF-type transcription factors in different abiotic stress responses. We have comprehensively discussed the application of advanced ground-breaking genome engineering tool, CRISPR/Cas9, to edit specific ERFs. We have also highlighted our on-going and published R&D efforts on multiplex CRISPR/Cas9 genome editing of negative regulatory genes for multiple abiotic stress responses in plant and crop models. The overall aim of this review is to highlight the importance of CRISPR/Cas9 and ERFs in developing sustainable multiple abiotic stress tolerance in crop plants.